Analysis of diagnosis and treatment interval of breast cancer patients attending Sultan Ahmad Shah Medical Centre @IIUM - Ling, Wilson; Che Alhadi, Shahidah; Mahno, Noor Ezmas; Ahmad, Azrin Waheedy; Sarif, Mat Salleh; Amjad, Nasser Muhammad; Kasian, Junaini; Elagili, Faisal; Othman, Faidzal; Che' Man, Mohamad (2023)
Introduction: Breast cancer is an ongoing issue that is plaguing many women worldwide. Early detection of breast cancer improve survival. In Malaysia, there is scanty data available to evaluate the acceptable time interval of diagnosis and treatment. This study aimed to analyze the diagnosis and treatment time interval of breast cancer patients attending SASMEC@IIUM. Materials and methods: A total of 87 participants were recruited in this retrospective cross-sectional study, conducted at SASMEC@IIUM, from January 2017 to December 2021. Those with recurrent breast cancer or known to have other cancers were excluded. Patients’ data were collected from clinical records and telephone interviews. Waiting times for presentation, referral, assessment, and initial treatment were documented. Results: From 87 participants, 99 % were female with a mean age of 57 years old (SD ± 11 years old). Majority were at the later stage of disease with 27% of patient were in stage III cancer and 30% had metastatic disease. The diagnostic interval was 13 days for stage IV, 14 days for stage III, 24.5 days for stage II and 70.5 days for stage I. In contrast, the treatment interval was 32 days for stage IV, 28 days for stage III, 23 days for stage II and 19 days for stage I. Statistically both diagnosis and treatment interval according to cancer staging was p = 0.082 and p = 0.273 which were statistically not significant. Conclusion: Adherent to standard international level treatment interval will provide the best oncological outcome. Our diagnosis and treatment interval were within the acceptable international standard of 28 days interval for diagnosis and treatment of breast cancer patients.